PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK ORGANISASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PERWAKILAN BADAN KEPENDUDUKAN DAN KELUARGA BERENCANA NASIONAL PROVINSI SULAWESI TENGAH - Taufiq, Liana Dewi (Katalogis, 2015)
This research intends to: 1) explore and analyze simultaneous effects of Individual characteristics, organizational characteristics, and work environment on officials performance in BKKBN office of Central Sulawesi; 2) explore and analyze the effects of individual characteristics on officials performance in BKKBN office of Central Sulawesi; 3) explore and analyze the effects of organizational characteristics on officials performance in BKKBN office of Central Sulawesi; 4) explore and analyze the effects of environment on officials performance in BKKBN office of Central Sulawesi. Based census-sampling technique, 78 people in the population selected as respondents. Based on multiple linear regression test, it is concluded that: 1) individual characteristics, organizational characteristics, and work environment simultaneously have positive and significant effects on the performance of officials in BKKBN office of Central Sulawesi; 2) individual characteristics partially have positive and significant effects on the performance of officials in BKKBN office of Central Sulawesi; 3) organizational characteristics have positive and significant effects on the performance of officials in BKKBN office of Central Sulawesi; 4) work environment has positive and significant effects on the performance of officials in BKKBN office of Central Sulawesi